Modeling of filtration of 2-types particles suspension in a porous medium - Galaguz Yuri; Safina Galina (MATEC Web of Conferences, 2017)
The filtration problem describes the process of concreting loose soil with a liquefied concrete solution. The filtration of 2-types particles suspension in a homogeneous porous medium with a size-exclusion particles retention mechanism is considered. The difference in the filtration coefficients of 2-types particles leads to the separation of the filtration domain into two zones, in one of which two types of particles are deposited and in another – only particles of one type are deposited. In this paper, the mobile boundary of two zones is calculated, and numerical solution of the problem is calculated.